2017
DOI: 10.1371/journal.pone.0189594
|View full text |Cite
|
Sign up to set email alerts
|

Mapping QTLs for grain yield components in wheat under heat stress

Abstract: The current perspective of increasing global temperature makes heat stress as a major threat to wheat production worldwide. In order to identify quantitative trait loci (QTLs) associated with heat tolerance, 251 recombinant inbred lines (RILs) derived from a cross between HD2808 (heat tolerant) and HUW510 (heat susceptible) were evaluated under timely sown (normal) and late sown (heat stress) conditions for two consecutive crop seasons; 2013–14 and 2014–15. Grain yield (GY) and its components namely, grain wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
50
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(58 citation statements)
references
References 41 publications
(54 reference statements)
8
50
0
Order By: Relevance
“…We believe that these are the true chromosomes that harbor leaf chlorophyll content QTLs responding to heat stress since they were only detected under heat stressed temperature and/or mapped using heat response of the trait. Previous studies also identified QTLs for heat stress tolerance traits, specifically at grain filling stage of wheat on chromosomes 2B, 2D, and 4A ( Paliwal et al, 2012 ; Acuña-Galindo et al, 2015 ; Bhusal et al, 2017 ). However, previous QTL studies conducted in wheat also identified QTLs for leaf chlorophyll content under heat stress on other chromosomes including 1B, 1D, 6A, and 7A ( Talukder et al, 2014 ), which were not detected at the seedling stage in the current study.…”
Section: Discussionmentioning
confidence: 91%
“…We believe that these are the true chromosomes that harbor leaf chlorophyll content QTLs responding to heat stress since they were only detected under heat stressed temperature and/or mapped using heat response of the trait. Previous studies also identified QTLs for heat stress tolerance traits, specifically at grain filling stage of wheat on chromosomes 2B, 2D, and 4A ( Paliwal et al, 2012 ; Acuña-Galindo et al, 2015 ; Bhusal et al, 2017 ). However, previous QTL studies conducted in wheat also identified QTLs for leaf chlorophyll content under heat stress on other chromosomes including 1B, 1D, 6A, and 7A ( Talukder et al, 2014 ), which were not detected at the seedling stage in the current study.…”
Section: Discussionmentioning
confidence: 91%
“…Due to the transformed genetic toolkit available in wheat, untangling the genetic architecture of traits by genome-wide association study (GWAS) and predicting performance by genomic selection (GS) have become feasible. Several GWAS analyses have been performed in wheat for plethora of traits including yield and yield components (Golabadi et al, 2011;Neumann et al, 2011;Bordes et al, 2014;Edae et al, 2014;Azadi et al, 2015;Assanga et al, 2017;Bhusal et al, 2017;Li et al, 2019). However, outcomes of these studies have hardly been applied in practical breeding programs.…”
Section: Introductionmentioning
confidence: 99%
“…Four additive QTLs have been reported for chlorophyll content on chromosomes 1B, 2D, 3B and 7D in wheat in heat and drought stress conditions (Tahmasebi et al 2016). Major QTLs for heat tolerance have also been reported on chromosomes 2A and 2B in wheat under heat stress condition (Bhusal et al 2017). In complex traits, it is recognized that epistatic effects and QTL 9 environment interactions are important genetic components (Rebetzke et al 2007).…”
Section: Introductionmentioning
confidence: 99%